Factors influencing the adoption of organic fertilizer by durian farmers : a case study of Srisaket Provice, Thailand - Kittipong Woraratpoka; Zulfiqar, Farhad; Himanshu, Sushil Kumar; Datta, Avishek; Yaseen, Muhammad; Royal Thai Government Fellowship (Pathum Thani, Thailand : Asian Institute of Technology, 2024)
This research explores the impact of demographic factors, including gender, age, family size, education, farm experience, land ownership, and fertilizer type, on the adoption of organic fertilizer among durian farmers. It also examines non-demographic factors such as economics, social dynamics, marketing, cultivation, and government policies that influence farmers' decisions and investigates the strengths, weaknesses, opportunities, and threats for the adoption of organic fertilizers by durian farmers. The research employs a combination of quantitative and qualitative methods to meet its objectives. Primary data collection involves surveys and interviews with cooperative leaders, while secondary data focuses on organic fertilizer adoption, support sources, and market facilities. The sample includes 60 durian farmers using organic fertilizers and 60 non adopters. Utilizing T-test analysis, One-way ANOVA, LSD analysis, Descriptive analysis, Ranking Descriptive Analysis (RDA), Logistic Regression, and a SWOT analysis are applied to data analysis. The research found the adoption of organic fertilizers among durian farmers in Thailand, revealing that age is the only demographic factor significantly correlated with adoption, indicating that younger farmers are more likely to embrace organic fertilizers. While there is a positive trend in eco-friendly farming methods among Thai durian farmers, wider adoption is needed, especially among older farmers, which can be achieved through government regulations, education, and support initiatives. The research identifies government policy as the most influential factor in adoption, with social, marketing, and cultivation factors also playing roles, and recommends that the government's support for organic fertilizers adoption among durian farmers can drive and motivate durian farmers to enhance their productivity by utilizing organic fertilizers in durian farming. The government has to focus on schemes where farmers benefit from education and training programs, financial incentives, technical assistance and support services, research and development, policy support and regulatory frameworks, and knowledge sharing and networking.
A Thesis submitted in partial fulfillment of the requirements for the degree of Master of Agribusiness Management in Agribusiness Management
Thesis (M. Am.) - Asian Institute of Technology, 2024
Keywords: Organic fertilizers; Durian -- Thailand